A dual fluorescence channel RAA-based CRISPR-Cas12a/Cas13a system for highly sensitive detection of Gyrovirus galga1 and Gyrovirus homsa1 - Dan Yu; Zhixun Xie; Yanfang Zhang; Zhiqin Xie; Qing Fan; Sisi Luo; Liji Xie; Meng Li; Tingting Zeng; Minxiu Zhang; Xiaofeng Li; You Wei; et al. (Virulence)
Gyrovirus galga1 (GyG1) and Gyrovirus homsa1 (GyH1) are the second and third most common gyroviruses identified, respectively, after chicken anaemia virus. They were first reported in 2011 and are currently prevalent worldwide. However, limited research on these pathogens and a lack of prevention and control strategies have necessitated the establishment of a rapid diagnostic technique to address new challenges in infectious diseases. Recombinase acid amplification (RAA) combined with CRISPR – Cas12a or CRISPR – Cas13a technology has major advantages for highly sensitive and rapid diagnosis. Specific targets can activate CRISPR–Cas trans-cleavage activity, resulting in non-specific cleavage of single-stranded DNA by the CRISPR – Cas12a complex and RNA cleavage by the CRISPR – Cas13a complex. In this study, for the first time, we combined RAA-based CRISPR – Cas12a and CRISPR – Cas13a systems for simultaneous differential diagnosis of GyG1 and GyH1 infection. The results showed that dual fluorescence channel RAA-based CRISPR – Cas12a/Cas13a technology could detect GyG1 and GyH1 within one hour, with a minimum detection limit of 1.5 copies of the target DNA standard/µL and no cross-reactivity with other avian pathogens. In addition, this method could be used for clinical detection, with the results exhibiting high consistency with those obtained by qPCR. These findings demonstrate that our RAA-based CRISPR – Cas12a/Cas13a dual-channel detection system can detect two different subtypes of gyrovirus in a sample with good specificity and high sensitivity, improving the detection efficiency and providing a new technique for the study of viral infection dynamics.